Table-like magnetocaloric effect and large refrigerant capacity in Gd65Mn25Si10-Gd composite materials for near room temperature refrigeration - Zhong, Xi Chun (2020)
Amorphous Gd65Mn25Si10 as well as crystalline Gd have technologically significant Curie temperature and large magnetic entropy change. Two types of composite materials Gd65Mn25Si10-Gd were fabricated: laminating Gd sheets and amorphous Gd65Mn25Si10 ribbons (multilayer composite) and hot pressing a mixture of amorphous Gd65Mn25Si10 thin ribbons, Gd particles and a small amount of Sn powders (bulk composite). A table-like magnetocaloric effect (MCE) in a wide, commercially useful, temperature span of 73 K (220 K-293 K) were observed in these composites. The values of full-width at half maximum of (−ΔSM) − T plots (ΔTFWHM) and enhanced refrigerant capacity (RC) for the multilayer and bulk composites are 212 K, 724 J/kg, and 248 K, 617 J/kg, respectively, for a field of 5 T. Large ΔTFWHM and RC values and the table-like (−ΔSM)max feature suggest that both multilayer and bulk Gd65Mn25Si10-Gd composites can meet the requirements of different magnetic refrigeration based on Ericsson-cycle.